Etude de la productivité des parcours de la zone d'Ain-Leuh (Moyen Atlas, plateau central). I. Effets de la fréquence d'exploitation et du taux de couvert arboré sur la productivité herbacée - Qarro, M; de Montard, F X (Agronomie, 1989)
Rough pastures in Middle Atlas spread over four bioclimatic levels: 1, Quercus ilex and Juniperus oxycedrus forest; 2, pure Quercus ilex forest; 3, Cedrus atlantica and Quercus ilex forest; 4, unsylvatic low grass, from 900 to 2 200 m above sea level. Dry matter production of grass was measured from and underneath the tree canopy in 1983 and 1984 in order to compare the effect of a variety of intervals between cuts and to measure shadow influence. Grass growth mainly occured from late January to early July; it began later at Cedrus-Quercus and low grass sites and stopped earlier at pure Quercus and Quercus-Juniperus sites, depending on longer frost persistence at highest levels, on earlier arrival of drought at lowest levels. Mean dry matter production was 2.5 kg h 1a d-! on light 30 cm deep soils at Quercus-Juniperus level and dolomitic soils at Cedrus-Quercus level. It was 5.5 kg ha-! d i- on colluvial soils at pure Quercus level and basaltic soil at lowgrass level Water balance and legume species abundance explained a great part of D.M. variance. Four cuts per year were more productive than three or five. Missing the earliest cuts resulted in much lower D.M. yields: a half with two cuts; three of five with an only cut per year. Shadow poorly reduced the yield up to a forest canopy cover of about 60%: from 35 to 65% cover, the canopy resulted in 30% fall in seasonal yield as water supply was not limiting, but had no effect as relative water deficit occurred. A pasture and forestry mixed system, aiming a canopy of 60 to 70% cover, would result in better conditions for cattle breeding and timber as a whole.
Keywords: clipping; dry matter; rythm; silvopastoral; water deficit